HUBUNGAN ANTARA IMUNOEKSPRESI P130CAS DENGAN KARSINOMA TIROID PAPILARIS - Mochamad Alex Sander (Universitas Muhammadiyah Malang, 2010)
Abstract Introduction: There are difficulties to determine follicular variants of papillary thyroid carcinomas if the pathological examination revealed no ground glass appearance in the nuclei/Orphan Annie eye, because the diagnosis of papillary thyroid carcinomas will established to the nuclei. The supporting diagnostic methods were needed to differ between variants follicular of papillary thyroid carcinomas and follicular thyroid carcinomas. Methods: The method of the research was observational analytic using cross sectional design with data that was taken retrospectively. This research investigates an immunoexpression of p130cas immunohistochemically in 31 paraffin-block samples included 8 of papillary thyroid carcinoma without node, 2 with positive node, 13 of papillary thyroid carcinomas follicular variant, and 8 of follicular thyroid carcinomas. The datas were analyzed using a statistic method (Chi square). Results: All papillary thyroid carcinomas and their variants were immunoreactive for p130cas, no positivity in follicular thyroid carcinomas. From Chi Square Test at confidence interval 95%, á = 0,05, and df = 12, we got x2 = 31,000 with p value < 0,001. Discussion: Immunoexpression of p130cas on immunohistochemically can help to diagnose of papillary thyroid carcinoma and their variants especially through FNAB (fine-neddle aspiration biopsy). Keywords : papillary carcinomas, p130cas, thyroid.